Data from: Are brood sex ratios adaptive? The effect of experimentally altered brood sex ratio on nestling growth, mortality, and recruitment - Szász, Eszter; Sarkadi, Fanni; Szöllősi, Eszter; Kopena, Renáta; Török, János; Rosivall, Balázs (Dryad, 2022)
Brood sex ratios (BSRs) have often been found to be non-random in respect
of parental and environmental quality, and many hypotheses suggest that
non-random sex ratios can be adaptive. To specifically test the adaptive
value of biased BSRs, it is crucial to disentangle the consequences of BSR
and maternal effects. In multiparous species, this requires
cross-fostering experiments where foster parents rear offspring
originating from multiple broods, and where the interactive effect of
original and manipulated BSR on fitness components are tested. To our
knowledge, our study on collared flycatchers (Ficedula albicollis) is the
first that meets these requirements. In this species, where BSRs had
previously been shown to be related to parental characteristics, we
altered the original BSR of the parents shortly after hatching by
cross-fostering nestlings among trios of broods, and examined the effects
on growth, mortality, and recruitment of the nestlings. We found that
original and experimental BSR, as well as the interaction of the two were
unrelated to the fitness components considered. Nestling growth was
related only to background variables, namely brood size and hatching rank.
Nestling mortality was related only to hatching asynchrony. Our results
therefore do not support that the observed BSRs are adaptive in our study
population. However, we cannot exclude the possibility of direct effects
of experimentally altered BSRs on parental fitness, which should be
evaluated in the future. In addition, studies similar to ours are required
on various species to get a clearer picture of the adaptive value of
non-random BSRs.
Data were collected in a nest-box breeding population of the collared
flycatcher (Ficedula albicollis) in the Pilis-Visegrádi Mountains, Hungary
(47°43′ N, 19°01′ E) in 2017-2021.
Keywords: FOS: Biological sciences; cross-fostering; fitness; Nestling development; offspring sex ratio; hatching asynchrony